Artificial Intelligence and Brain Research: Neural Networks, Deep Learning and the Future of Cognition - Krauß, Patrick (Springer, 2024)
How does artificial intelligence (AI) work and are there parallels to the human brain? What do natural and artificial intelligence have in common, and what are the differences? Is the brain nothing more than a biological computer? What are neural networks and how can the term deep learning be explained simply? Since the cognitive revolution in the middle of the last century, AI and brain research have been closely intertwined. There have been several spectacular breakthroughs in the field of AI in recent years, from alphaGo to DALL-E 2 and ChatGPT, which were completely unthinkable until recently. However, researchers are already working on the innovations of tomorrow, such as hybrid machine learning or neuro-symbolic AI. But what does this actually mean? Based on current research findings and exciting practical examples, this non-fiction book provides an understandable introduction to the basics and challenges of these fascinating disciplines. You will learn what neuroscience and psychology know about how the brain works and how artificial intelligence works. You will also learn how AI has revolutionized our understanding of the brain and how findings from brain research are used in computer science to further develop AI algorithms. Discover the fascinating world of these two disciplines. Find out why artificial intelligence and brain research are two sides of the same coin and how they will shape our future.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Algorithms; Artificial intelligence (AI); Autonomous driving; Awareness; Black Box Problem; Brain research; ChatGPT; alphaGo; DALL-E 2; Cognitive revolution; Cognitive science; Computer science; Deep Learning; Language processing; Machine Learning; Machine learning; Mind Brain Machine; Neural networks; Neurobiology; Neurosciences; Psychology; Robot